Estimation of residue degradation of cypermethrin and chlorpyrifos in brinjal, tomato and cauliflower under supervised field trial - Ahmed, Md Sultan; Hossain Prodhan, Mohammad Dalower; Begum, Afroza; Afroze, Marina; Sarker, Debasish (Asian-Australasian Journal of Bioscience and Biotechnology, 2021)
A study was carried out to detect and estimate the residue of cypermethrin and chlorpyrifos in brinjal, tomato and cauliflower using Gas Chromatography (GC) coupled with Electron Capture Detector (ECD) and Flame Thermionic Detector (FTD). Three supervised field trials were conducted and sprayed with the recommended dose of cypermethrin (1 ml/L of water) and chlorpyrifos (3 ml/L of water) in three vegetables by knapsack sprayer. Samples were collected at 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, and 11 days after spray (DAS). The quantity of cypermethrin residue was above EU-MRLs (Maximum Residue Limit set by European Union) up to 4 DAS with 0.538 mg/kg in cauliflower; 3 DAS with 0.508 mg/kg in brinjal and 0.695 mg/kg in tomato. The quantity decreased down 0.328-0.019 mg/kg in cauliflower (4-9 DAS); 0.098-0.012 mg/kg (4-7 DAS) in brinjal and 0.458-0.022 mg/kg (4-7 DAS) in tomato which were below EU-MRLs (0.5 mg/kg). The quantity of chlorpyrifos residue was above EU-MRLs up to 9 DAS with 0.012 mg/kg in cauliflower but in brinjal and tomato, the detected quantities were above EU-MRLs up to 7 DAS with 0.029 mg/kg and 0.017 mg/kg residue. No residue was detected from brinjal and tomato samples collected at 8 DAS. But in cauliflower, no residue was detected at 10 days after spray. So, brinjal, tomato and cauliflower can be harvested safely at 4 DAS and 5 DAS for cypermethrin and in case of chlorpyrifos it was 8 DAS in brinjal and tomato and 10 DAS in cauliflower. Asian Australas. J. Biosci. Biotechnol. 2021, 6 (2), 60-67